Programming Techniques through C. - Venkateshmurthy, Dr. M. G. (1900)
A hands-on book on rudiments of programming, Programming Techniques through C: A Beginner's Companion teaches you the techniques of solving problems from simpler ones like "finding out the area of a triangle" to more involved ones like "sorting and searching". The visual approach to solve problems in a step-by-step manner through flowcharts makes it easy for the beginners to solve problems and write programs using the C programming language. The emphasis is on problem solving procedures rather than learning a language.
Functions to Compute Mean and Variance and Hence to Compute Standard Deviation of Given Set of Numbers -- Functions to Read and Write one Dimensional Array -- Function to Sort an Array Using Bubble Sort Method -- Function to Search for a Required Element Using Binary Search Method -- Functions to Sort a Given Unsorted Array Using Selection Sort -- Functions to Read, Write and Compute Trace of Given Matrix -- Functions to Compute Sum of Each Row, Sum of Each Column and Sum of All Elements of Given Matrix -- Functions to Read, Write and Compute Product of Two Given Matrices -- Program to Search for Required Element in a Given Unsorted Array Using Functions on Separate File -- Understanding the Meaning of Local and Global Variables -- Function to Swap Contents of Two Variables-The Wrong One -- Exercises -- Pointers -- Understanding Prelims of Pointers -- Understanding Pointer Expressions, Pointer-to-Pointer and Null Pointer -- Finding Sum of all Elements of Array Using Pointers -- Function to Swap Contents of Two Variables Using Pointers -- Solving Quadratic Equation-Using Functions and Pointers -- Exercises -- Structures -- Defining a Structure, Declaring, Structure Variables, Assigning Values to Structure Members and Printing Out Structure Member Values -- Array of Structure Variables: Listing Names of Students Who Have Scored More Than 60% of Total Marks in Three Subjects Using Structure Variables -- Sum of Two Complex Numbers-Passing Structure Variable to Function -- Array of Structure Variables with a Structure as Member of Another Structure -- Exercises -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books